2022
DOI: 10.1103/physreve.106.024118
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed graphs achieve unit transport efficiency without environmental noise

Abstract: Coherent transport of an excitation through a network corresponds to continuous-time quantum walk on a graph, and the transport properties of the system may be radically different depending on the graph and on the initial state. The transport efficiency, i.e., the integrated probability of trapping at a certain vertex, is a measure of the success rate of the transfer process. Purely coherent quantum transport is known to be less efficient than the observed excitation transport, e.g., in biological systems, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The tr-XRD experiments were performed at the Bernina endstation [28,29] of the ARAMIS branch of SwissFEL at the Paul Scherrer Institute (Switzerland). The tr-RSXD experiments were performed at the Furka endstation, which is a new endstation for time-resolved studies in condensed matters at the Athos branch of SwissFEL at Paul Scherrer Institute [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…The tr-XRD experiments were performed at the Bernina endstation [28,29] of the ARAMIS branch of SwissFEL at the Paul Scherrer Institute (Switzerland). The tr-RSXD experiments were performed at the Furka endstation, which is a new endstation for time-resolved studies in condensed matters at the Athos branch of SwissFEL at Paul Scherrer Institute [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Using similar arguments, Bose et al [9] have shown that the single link removal also allows perfect state transfer between the two nodes. The mechanism behind this counter-intuitive result is the elimination of destructive interference by removal of the single interaction [8,9,12,15,20,40]. The problem could also be addressed by using graph spectral theoretical concepts in terms of the eigenvalues and eigenvectors of the adjacency matrix A of the network.…”
Section: Introductionmentioning
confidence: 99%
“…CTQWs are especially useful to model physical phenomena such as quantum transport of energy in quantum biological systems, quantum routing, and quantum state transfer. [60][61][62][63][64][65][66] They have been both realized and simulated experimentally on different platforms, such as photons, [67][68][69] trapped atoms and ions, 70,71 waveguide arrays, [72][73][74][75] microwaves, 76 and nuclear magnetic resonance. 77 In all these tasks, fine tuning of the Hamiltonian parameters is required in order to achieve reliable and satisfactory results.…”
Section: Introductionmentioning
confidence: 99%